A New Benzylated Fatty Acid Amide Amphoteric Surfactant Derived from Hydrogenated Castor Oil with Ultra‐Low Interfacial Tension between Crude Oil and Brine. Issue 3 (27th February 2021) - Gao, Cheng‐Long; Gang, Hong‐Ze; Liu, Jin‐Feng; Mu, Bo‐Zhong; Yang, Shi‐Zhong
Abstract: Hydrogenated castor oil from castor oil is promisingly used as raw materials for lubricants, coatings, cosmetics, and pharmaceutics due to high melting point and stable physical properties. However, the chemical modification of the hydrogenated castor oil has been rarely investigated. Here, we report a N‐phenyl‐fatty‐amido‐1‐propyl‐ N, N ‐dimethyl‐amino‐carboxyl‐betaine surfactant derived from hydrogenated castor oil with excellent interfacial properties through a rapid synthetic process, including direct alkylation, amidation, and quaternization. The interfacial tension between crude oil and brine was ultra‐low for a low dosage of 0.007 g L −1 of surfactant in aqueous solution without any alkali addition, which implies a potential application in enhanced oil recovery.